The role of geographical environment during the wars in Bulgaria in the second half of the 19th century - Faszcza, Dariusz (Armia kontra natura, 2020)
The knowledge of geographical conditions is one of the main requirements for planning military operations at each command level. The natural environment enforces the variety of combat techniques. It is a truism, therefore, to say that every military historian reconstructing the course of wars or war campaigns should analyze the impact of natural conditions on the battle planning process and its course. The article presents the characteristics of Bulgarian area and the impact of geographical conditions on the course of military operations during the Russian-Turkish war of 1877–1878 and the Serbian-Bulgarian war of 1885. Although they were two different conflicts in terms of duration, number of forces and direction of conduct, their example shows the problems faced by fighting armies at the time. We are dealing with issues related to overcoming the swollen waters of Danube and battlefields abounding in hills and mountain passages difficult to access. Not without significance were weather issues, which influenced the course of the fight and the possibilities of supplying troops.